Changes in Rocky Intertidal Community Structure During a Marine Heatwave in the Northern Gulf of Alaska - Weitzman, Benjamin; Konar, Brenda; Iken, Katrin; Coletti, Heather; Monson, Daniel; Suryan, Robert; Dean, Thomas; Hondolero, Dominic; Lindeberg, Mandy (Frontiers in Marine Science, 2021)
Marine heatwaves are global phenomena that can have major impacts on the structure and function of coastal ecosystems. By mid-2014, the Pacific Marine Heatwave (PMH) was evident in intertidal waters of the northern Gulf of Alaska and persisted for multiple years. While offshore marine ecosystems are known to respond to these warmer waters, the response of rocky intertidal ecosystems to this warming is unclear. Intertidal communities link terrestrial and marine ecosystems and their resources are important to marine and terrestrial predators and to human communities for food and recreation, while simultaneously supporting a growing coastal tourism industry. Given that current climate change projections suggest increased frequency and duration of marine heatwaves, monitoring and understanding the impacts of heatwaves on intertidal habitats is important. As part of the Gulf Watch Alaska Long-Term Monitoring program, we examined rocky intertidal community structure at 21 sites across four regions spanning 1,200 km of coastline: Western Prince William Sound, Kenai Fjords National Park, Kachemak Bay, and Katmai National Park and Preserve. Sites were monitored annually from 2012 to 2019 at mid and low tidal strata. Before-PMH (2012–2014), community structure differed among regions. We found macroalgal foundation species declined during this period mirroring patterns observed elsewhere for subtidal habitat formers during heatwave events. The region-wide shift from an autotroph-macroalgal dominated rocky intertidal to a heterotroph-filter-feeder dominated state concurrent with the changing environmental conditions associated with a marine heatwave event suggests the PMH had Gulf-wide impacts to the structure of rocky intertidal communities. During/after-PMH (2015–2019), similarities in community structure increased across regions, leading to a greater homogenization of these communities, due to declines in macroalgal cover, driven mostly by a decline in the rockweed, Fucus distichus, and other fleshy red algae in 2015, followed by an increase in barnacle cover in 2016, and an increase in mussel cover in 2017. Strong, large-scale oceanographic events, like the PMH, may override local drivers to similarly influence patterns of intertidal community structure.